Pemanfaatan Media Google Colaboratory Pada Mata Pelajaran Informatika di SMA Negeri 5 Pekanbaru - Haana Udtari Anjani; Vitriani Vitriani; Mulya Hastuti (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to fill the knowledge gap by analyzing the utilization of Google Collaboratory learning media on utilization of Google Collaboratory learning media in informatics subjects in the high school environment. informatics in a secondary school environment. Through a deeper understanding about the experience of using this platform, it is expected to be identified benefits, constraints, and effective strategies in optimizing the utilization of Google Collaboratory as a learning media. Google Collaboratory as an effective and efficient learning media in informatics learning. This research will use a qualitative approach with a case study research design. with a case study research design. The qualitative approach is chosen to get an in-depth understanding of the experience of using Google Collaboratory in informatics learning. Collaboratory in informatics learning. The case study design was chosen because it allows researchers to investigate phenomena in a real context, such as the utilization of Google Collaboratory in a learning situation in a secondary school. secondary school. This research provides a deeper understanding of the potential and challenges in the utilization of Google Collaboratory as a medium for learning Informatics in secondary school. Informatics in secondary schools. The findings of this research can be the basis for the development of more innovative and effective learning practices in the future. context of information technology education in the future.